The influence of diamond-mining industry waste on soil geochemistry and the development of salinization processes - Vasileva, Tatiana; Legostaeva, Yana; Shadrinova, Olesya; Ivanov, Egor (Frontiers in Environmental Science, 2025)
IntroductionMining in the Arctic induces severe environmental transformations, particularly soil salinization, which threatens the fragile ecosystems of permafrost-affected landscapes. This study investigates the mechanisms of this process in the Daldyn-Alakit region (Western Yakutia), focusing on the interaction between the geogenic potential of waste rocks and technogenic triggers.MethodsWe conducted an integrated analysis of technogenic massifs (waste rock dumps, tailings) and soils at the Udachninsky and Aikhal mining and processing plants. The methodology included petrographic microscopy, X-ray diffraction (XRD) analysis, geochemical analysis of major oxides and trace elements, and ion chromatography of water extracts to characterize salinity.ResultsWe identified that gypsum-bearing dumps at the Aikhal site present a high inherent risk for sulfate salinization, while the kimberlites contribute primarily to trace metal (Ni, Cr) enrichment. However, the actual widespread salinization is driven by technogenic factors: the primary activator for chloride salinization is the surface interaction with highly mineralized brines from injection sites and tailings storage facilities. The secondary driver is the enhanced weathering of waste dumps, releasing sulfates.DiscussionOur results demonstrate that salinization type is not a simple function of waste rock composition but a complex interplay between inherent geochemical properties and mining-induced pathways. This finding is crucial for developing targeted reclamation strategies.